LEAN MANUFACTURING AND ITS IMPACT ON THE PRODUCTIVE SECTOR - dos Santos, João Pedro David; Cadioli, Luiz Paulo (Revista Interface Tecnológica, 2022)
This article presents bibliographical research as a theoretical foundation and seeks to present in a very succinct way the main definitions on Lean Manufacturing and its importance for organizations, highlighting the benefits of its implementation. Through the use of this tool, new concepts can be developed, including minimizing costs and eliminating waste, aiming at optimizing the production flow and consequently achieving product quality. The structure of the article is divided as follows: basic definitions, a brief history, its evolution, the main fundamentals of Lean Manufacturing, example demonstration of the application of this methodology, where the benefits acquired when using it in a sector are defined. production of powder paint, and its connection with basic concepts of sustainability. The methodological procedures for carrying out this work, the effects obtained with the implementation of the methodology and the final considerations were also presented.
Keywords: Lean Manufacturing; Impacts; Fundamentals; Implantation